Risk of sick leave and disability pension in working-age women and men with knee osteoarthritis. Issue 3 (7th June 2012) - Hubertsson, Jenny; Petersson, Ingemar F; Thorstensson, Carina A; Englund, Martin
Abstract : Objectives: To investigate sick leave and disability pension in working-age subjects with knee osteoarthritis (OA) compared with the general population. Methods: Population-based cohort study: individual-level inpatient and outpatient Skåne Health Care Register data were linked with data from the Swedish Social Insurance Agency. In 2009 all working-age (16–64 years) Skåne County residents who in 1998–2009 had been diagnosed with knee OA (International Classification of Diseases-10 code M17) were identified and their sick leave and disability pension in 2009 related to those of the general working-age population (n=789 366) standardised for age. Results: 15 345 working-age residents (49.6% women) with knee OA were identified. Compared with the general population, the RR (95% CI) of having had one or more episodes of sick leave during the year was 1.82 (1.73 to 1.91) for women and 2.03 (1.92 to 2.14) for men with knee OA. The corresponding risk for disability pension was 1.54 (1.48 to 1.60) for women and 1.36 (1.28 to 1.43) for men with knee OA. The annual mean number of sick days was 87 for each patient with knee OA and 57 for the general population (age- and sex-standardised). Of all sick leave and disability pension in the entire population, 2.1% of days were attributable to knee OA or associated comorbidity in the patients with knee OA (3.1% for sick leave and 1.8% for disability pension). Conclusions: Subjects with doctor-diagnosed knee OA have an almost twofold increased risk of sick leave and about 40–50% increased risk of disability pension compared with the general population. About 2% of all sick days in society are attributable to knee OA.